Profil Perilaku Keuangan Mahasiswi: Menggunakan Pendekatan K-Means Clustering - Kartika Kinanti; Yulian Ade Chandra; Aji Prasetyo Suyono (Sekolah Tinggi Ilmu Ekonomi GICI, 2025)
This study aims to profile financial behavior among female students of ITB Widya Gama Lumajang using the K-Means clustering method, with a focus on financial literacy, consumption patterns, financial management, and the phenomenon of Fear of Missing Out (FOMO). A quantitative approach was employed through cluster random sampling, involving 100 active female student respondents. Data were collected using a structured questionnaire with semantic scale measurements, which had been tested for validity and reliability. The results of the analysis indicate the formation of four clusters, labeled Good, Moderate, Poor, and Extreme, reflecting the heterogeneity of respondents’ financial behavior. The findings show that female students with higher levels of financial literacy tend to demonstrate more structured financial management, better control over consumption, and lower levels of FOMO. Conversely, uncontrolled consumption patterns and high levels of FOMO contribute to the emergence of an extreme behavioral group. These findings are expected to provide an empirical foundation for the development of more targeted financial education strategies, as well as to serve as a basis for institutional decision-making aimed at minimizing impulsive financial behavior among female students in the digital era.